2023
DOI: 10.3390/ijms241411756
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Definition of the Molecular Hallmarks of Idiopathic Membranous Nephropathy in Serum Proteome: A DIA-PASEF Approach

Abstract: Idiopathic membranous nephropathy (IMN) is a pathologically defined disorder of the glomerulus, primarily responsible for nephrotic syndromes (NS) in nondiabetic adults. The underlying molecular mechanisms are still not completely clarified. To explore possible molecular and functional signatures, an optimised mass spectrometry (MS) method based on next-generation data-independent acquisition combined with ion-mobility was applied to serum of patients affected by IMN (n = 15) or by other glomerulopathies (PN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…nLC-ESI MS/MS analyses were performed coupling the nLC system online with a timsTOF fleX (Bruker Daltonics, Bremen, Germany) mass spectrometer using a CaptiveSpray source, as already described with some modifications. , BFPE and FFPE renal samples at different fixation time points were analyzed with the Evosep One LC system (Evosep Biosystems, Odense, Denmark): 400 ng of peptides for each sample were loaded into a disposable trap column, Evotip Pure (Evosep Biosystems, Odense, Denmark), following the manufacturer protocol. Desalted and concentrated peptides were separated into an analytical 8 cm column (PepSep C18, 8 cm Performance column, a particle size of 1.5 μm, and an internal diameter of 150 μm) at a temperature of 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…nLC-ESI MS/MS analyses were performed coupling the nLC system online with a timsTOF fleX (Bruker Daltonics, Bremen, Germany) mass spectrometer using a CaptiveSpray source, as already described with some modifications. , BFPE and FFPE renal samples at different fixation time points were analyzed with the Evosep One LC system (Evosep Biosystems, Odense, Denmark): 400 ng of peptides for each sample were loaded into a disposable trap column, Evotip Pure (Evosep Biosystems, Odense, Denmark), following the manufacturer protocol. Desalted and concentrated peptides were separated into an analytical 8 cm column (PepSep C18, 8 cm Performance column, a particle size of 1.5 μm, and an internal diameter of 150 μm) at a temperature of 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…According to a recent study, upregulated biotinidase levels were found in idiopathic membranous nephropathy (IMN), i.e., a pathologically defined disorder of the glomerulus, which is primarily responsible for nephrotic syndromes (NSs) in nondiabetic adults. According to the authors, theirs was the first study correlating biotinidase and IMN, and the finding might deserve further investigation [ 181 ]. In another recent study, by employing drug database screening and AutoDock validation, the authors proposed that prostaglandin, valsartan, “biotin A”, luteolin, and curcumin might be potential drugs for antagonizing the plasminogen activator, urokinase receptor (PLAUR), which was identified as an effective diagnostic and possible therapeutic marker for atherosclerosis lesion progression [ 182 ].…”
Section: Further Perspectivesmentioning
confidence: 99%